Shift work is significantly and positively associated with dementia: A meta-analysis study - Lee, Kuo-Wei; Yang, Chen-Cheng; Chen, Chun-Hung; Hung, Chih-Hsing; Chuang, Hung-Yi (Frontiers in Public Health, 2023)
Background Shift work may disrupt the sleep and wake cycles and negatively affect physical and mental health. Dementia is a neurodegenerative disorder with progressively declining cognition that is receiving increasing attention. Studies on the association between shift work and dementia are rare. Herein, we conducted a meta-analysis to investigate the association between shift work and dementia. Materials and methods This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We searched the PubMed, Embase, and Web of Science databases using a related set of keywords. The inclusion criteria were as follows: (1) adult employees working in a factory, company, or organization; (2) exposure to shift work/non-shift work; and (3) outcome of dementia based on examination or assessment. A meta-analysis using a fixed-effects model was performed. The hazard ratio of dementia was compared between shift workers and non-shift workers. Results Five studies were included in the quantitative synthesis, and two were selected for further meta-analysis. A random-effects model showed a modest association between shift work and an increase in dementia cases (pooled hazard ratio = 1.13; 95% confidence interval: 1.04–1.23; p = 0.04). This association also occurred in night workers for more than 1 year. Conclusion Shift work and long-term night work were modestly associated with a higher risk of developing dementia. Avoiding long-term night shifts may be effective in reducing dementia risk. Further studies are required to confirm this hypothesis.